Canadian International Petroleum Conference 2004
DOI: 10.2118/2004-222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SAGD Performance in the Presence of Non-Condensable Gases

Abstract: In the steam assisted gravity drainage (SAGD) process, the addition of small amounts of non-condensable gases to steam may improve oil recovery. The gas accumulates at the top of the reservoir where it provides an insulation effect and forces the steam chamber to spread laterally. The result is a more efficient use of steam and the potential for greater recovery of oil.Six experiments were conducted in two different geometries to study the effect of non-condensable gas on the performance of SAGD. These experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
2
6
0
1
Order By: Relevance
“…Oil recovery is the highest for steam-only SAGD compared to all the solvent(s)-aided SAGD process. This finding is also found in the laboratory SAGD experiments (Canbolat et al, 2004). Overall, the best result for the solvent(s)-aided SAGD process (including one solvent addition, double and triple solvent mixture addition) is achieved with 5% volume addition of C 4 H 10 in the C 4 H 10 -SAGD process.…”
Section: Co 2 -C 3 H 8 -C 4 H 10 -Sagd Processsupporting
confidence: 78%
“…Oil recovery is the highest for steam-only SAGD compared to all the solvent(s)-aided SAGD process. This finding is also found in the laboratory SAGD experiments (Canbolat et al, 2004). Overall, the best result for the solvent(s)-aided SAGD process (including one solvent addition, double and triple solvent mixture addition) is achieved with 5% volume addition of C 4 H 10 in the C 4 H 10 -SAGD process.…”
Section: Co 2 -C 3 H 8 -C 4 H 10 -Sagd Processsupporting
confidence: 78%
“…Reduced steam-chamber growth and oil rates were observed in the presence of NCG in other experiments. 4 However, comparable oil recoveries were observed with and without NCG in core plug experiments. Other sets of experiments to evaluate the wind-down process by injecting NCG after SAGD resulted in a recovery of 12.5%.…”
Section: Introductionmentioning
confidence: 69%
“…The need for high volumes of steam, particularly in thin, low-quality reservoirs, is a significant restriction of SAGD due to the requirement of continuous steam production on the surface. This could be avoided by adding noncondensable gases (NCG) such as carbon dioxide (CO 2 ) or methane (CH 4 ) (i.e., the steam and gas push (SAGP) mechanism) or additionally by injecting liquefied petroleum gases such as propane (C 3 H 8 ) or n -butane ( n -C 4 H 10 ) (i.e., the vapor extraction (VAPEX) process). , In steam and gas push (Figure ), NCG such as carbon dioxide (CO 2 ), methane (CH 4 ), and nitrogen (N 2 ) are coinjected with steam. Because NCG have a lower density than condensate steam, they begin to rise within the reservoir and accumulate at the top of the depletion chamber …”
Section: Introductionmentioning
confidence: 99%
“…Flue gas, usually composed of carbon dioxide and nitrogen, has the properties of noncondensate gas that experiences no obvious condensation (Dong et al, 2017), can steadily exist in the stream chamber (Bagci and Gumrah, 2004;Li et al, 2019;Yuan et al, 2010) to migrate to the top of the steam zone to provide a barrier to reduce heat loss (Heron et al, 2008), and diminish the pressure of steam chamber (Yee and Stroich, 2004). In addition, some heat can be transferred to cold oil to promote the development of the steam chamber again to enhance the recovery factors (Aherne and Birrell, 2002;Canbolat et al, 2004;Wang et al, 2017). Non-Condensable Gasses not only can enhance the thermal efficiency of SAGD (Liu et al, 2012), but also can enhanced gas from shale layers recovery, Davarpanah and Mirshekari (2019) proposed a modified unipore diffusion model to study adsorption of methane and carbon dioxide at different pressure ranges, the result shows that the production of gas from shale layers is increased because of methane and carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the heat spread ranges of steam zone and hot water zone are expanded because of injecting flue gas, and the heat utilization rate was improved. The flue gas can accumulate at the top of the reservoir where it provides an insulation effect and forces the steam chamber to spread laterally (Canbolat et al, 2004). Ahmadi (2015) utilized numerical simulation method to compare with effect for EOR different gas injection methods (N 2 , CO 2 , produced reservoir gas, and flue gas), and found that the ultimate oil recovery was greatest for flue gas injection.…”
Section: Introductionmentioning
confidence: 99%